Potential use of salivary TNF-α as a vaccine-induced pain biomarker in people with cerebral palsy and communication disorders. - Álvaro Sabater-Gárriz; José Joaquín Cerón; Pedro Montoya; Inmaculada Riquelme (PLoS ONE)
Background Pain in people with cerebral palsy (CP) has been classically underestimated and poorly treated, particularly in individuals with impaired communication skills. Objective To analyze changes in different salivary metabolites and pain behavior scales after a painful procedure in adults with CP and adults with typical development. Methods Salivary levels of sTNF-α, sIgA, Cortisol, FRAP, ADA and Alpha Amylase, as well as 3 observational pain scales (Wong-Baker, Non-Communicating Adults Pain Checklist and Facial Action Coding System) were assessed before and after an intramuscular injection in 30 Individuals with CP and 30 healthy controls. Video recording of face expression was performed during the procedure for offline analysis. Results Pain in subjects with CP was higher than in healthy controls after the intramuscular injection as displayed by observational scales. sTNF-α experienced a significant post-stimulus increase in both groups and that increase shows a tendency to correlate with the observational scales scores. Other biomarkers classically associated with stress (cortisol, Alpha Amylase) remain stable. Conclusion sTNF-α might be a promising pain indicator. Further research using controlled painful stimuli of greater intensity and pain self-reports, would be necessary to better understand its use as a pain biomarker.